Morphometric studies on postnatal development of testis of Indian 'Murrah buffalo (Bubalus bubulis) - Malhi, P S; Pawar, H S; Roy, K S; Guraya, S S (The Indian Journal of Animal Sciences, 2012)
Morphometric studies have been made on the testis of 20 Murrah buffaloes during postnatal development. Testicular weight inrelation to body weight and testicular volume, increased from 0.01 % to 0.07% and 1.05 to 235.68 cm3 from 1day-old to adult (>6 years) buffalo bulls respectively. Tubular volume percentage showed initial decrease from 77.0% at birthto 61.0% at 6 months of age and again increased to 81.0% in adults. Tubular diameter showed increase from birth (50.10µ) toadult (221.13µ), Buffalo bulls attained puberty at 3-3.5 years of age. Total seminiferous tubular length, an index of thelevel of sperm production, was 4186µ in adults and total surface area was 2.90 2 in adults.